2012
DOI: 10.15218/zjms.2012.0038
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of human brucellosis in Erbil city

Abstract: Background and objectives: Brucellosis is an acute or chronic illness manifested principally by chills and fever. Occasionally, chronic relapsing febrile episodes occur. Brucellosis is endemic in animal and humans are infected incidentally. The aim of the study was to examine the incidence of brucellosis in Erbil City, study the relation between the rate of infection and a number of predisposing factors. Methods: Blood samples were collected from (2085) patients suspected of having brucellosis attending, Erbil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
(6 reference statements)
3
5
0
Order By: Relevance
“…In the current study, the highest rate of brucellosis (22.7%) was observed in the age group 21-30 years. Comparable findings were reported from different studies locally and worldwide (3,(23)(24)(25) . This would be expected because the brucellosis is an occupational disease and this age group exposed longer to risk factors related to their occupation.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In the current study, the highest rate of brucellosis (22.7%) was observed in the age group 21-30 years. Comparable findings were reported from different studies locally and worldwide (3,(23)(24)(25) . This would be expected because the brucellosis is an occupational disease and this age group exposed longer to risk factors related to their occupation.…”
Section: Discussionsupporting
confidence: 52%
“…This finding was in agreement with other studies in the region. Although some studies showed that more males were affected than females (26,27) , other studies revealed that the infection of brucellosis is predominant among females than males (2,25,28) . It is obvious in our region that females are more likely involved in household than males.…”
Section: Discussionmentioning
confidence: 99%
“…We found an association between human brucellosis and livestock contact with a statistically significant difference. This finding is in agreement with another study from Erbil [22] and indicates an important role of livestock in the epidemiology of human brucellosis in this province. Further studies to determine which species of livestock are the reservoirs for Brucella spp.…”
Section: Discussionsupporting
confidence: 93%
“…The current study showed the prevalence of probable brucellosis was 12.3% among suspected patients in Erbil-Kurdistan Iraq. A study conducted in the same hospital (Rizgari Hospital at Erbil) in 2012 reported a 10.7% prevalence which is close to the present study [22]. A slightly higher prevalence was found in another study conducted in Azadi general hospital in Duhok-Kurdistan, Iraq in 2017 with a seroprevalence rate of 17.8% [23].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation